2022
DOI: 10.5334/gh.1100
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Duration and Hypertension among Adults in Southwest China

Abstract: Objective: This study aimed to evaluate the association between sleep duration and hypertension among adults in southwest China.Methods: Baseline variables were collected from a representative sample of 20,053 adults aged 23-98 years in southwest China who received physical examinations from January 2019 to December 2020. All participants were categorized into either a hypertension group or a non-hypertension group. Sleep duration was classified as short (<6 h/day), normal (6-8 h/day),or long (>8 h/day). Basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
(22 reference statements)
0
6
1
Order By: Relevance
“…In the group of middle-aged people (45-59 years) or older adults, there were no connections between sleep duration and hypertension that were statistically significant (60-79 years). These results were in contrast with Southwest China by Jie He and Quan He [18], who reported shows a short sleep duration (6h/day) is associated with a higher risk of hypertension, indicating that sleep aids in preventing hypertension. They stated that 51.2% of people had hypertension overall.…”
Section: [23] Acontrasting
confidence: 84%
See 2 more Smart Citations
“…In the group of middle-aged people (45-59 years) or older adults, there were no connections between sleep duration and hypertension that were statistically significant (60-79 years). These results were in contrast with Southwest China by Jie He and Quan He [18], who reported shows a short sleep duration (6h/day) is associated with a higher risk of hypertension, indicating that sleep aids in preventing hypertension. They stated that 51.2% of people had hypertension overall.…”
Section: [23] Acontrasting
confidence: 84%
“…The main topic of most of these studies ranged from the relation between sleeping time, sleeping deprivation, short sleeping duration, and hypertension was included among them. Five studies were crosssectional [16][17][18][19][20], while three were designed longitudinally [21][22][23]. The studies' samples ranged in size from 2887 to 43 655 people.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from China discovered that long sleep duration was signi cantly associated with hypertension; however, this association was not obvious between short sleep duration and hypertension [30] . He et al found that a short sleep duration was related to an increased risk of hypertension [31] . These are the possible indirect factors of the relationship between sleep and eGFR in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Uniaxial compression characteristics, as one of the indispensable indexes to measure the basic physical and mechanical properties of rocks, are widely used in various engineering practices and scientific research work because of its relatively simple and clear test principles and easily realized test equipment. He et al (2022) carried out uniaxial compression test on sandstone, and found that with the increase of moisture content, the nonlinear characteristics of the rock stress-strain curve at the initial stage and the drop phenomenon after the strength peak became more obvious, and the sample changed from splitting failure to shear failure. Song et al (2021) established a sandstone deterioration model under dry wet cyclic loading through uniaxial compression test and acoustic emission testing technology.…”
Section: Introductionmentioning
confidence: 99%